Circulating tumour cell combined with DNA methylation for early detection of hepatocellular carcinoma - Liang, Wenjin; Xu, Zhigao; Kong, Fangyu; Huang, Xiao; Xiao, Yuxin; Zhou, Wei; Ye, Shaojun; Ye, Qifa (Frontiers in Genetics, 2022)
Background: The inadequate early detection strategies makes hepatocellular carcinoma (HCC) patients with poor prognisis. Therefore, more effective detection methods are urgently needed for early detection and early intervention of HCC. Methods：17 cases of suspected HCC patients and 11 cases of HBV-related decompensated cirrhosis (HBV-DeCi) patients were enrolled. For each patient, 5 mL blood sample was separated into circulating tumor cells (CTCs) and plasma, CTCs were stained with Diff staining for counting. Plasma was used for extracting cell free DNA (cfDNA) and then analyzed by qMSP assay. Ct values were recorded for GNB4 and Riplet as target genes and β-actin as an endogenous reference gene. Finally, clinical efficacy of CTC count combined with GNB4/Riplet methylation detection for early diagnosis of HCC was analyzed. Results: The CTC of HCC patients has pleomorphic characteristics, but it’s difficult to distinguish from other blood cells with non-obviously pleomorphic of CTC. Although a small number of CTCs can also be detected in HBV-DeCi patients (control group), the number is significantly lower than that in HCC patients, the sensitivity and specificity of CTC for HCC detection were 70.6% and 90.9% (AUC= 0.81). The Ct values of GNB4 and Riplet methylation were significantly different between HCC patients and control group patients. When CTC combined with two genes, the AUC value was significantly increased to 0.98, the sensitivity was 88.2%, and the specificity was 100%. Conclusion: Our study has developed a novel test that CTC count combined with GNB4/Riplet methylation detection and showed its high performance for early diagnosis of HCC.